Impact of Nutrition on Blood Pressure and Body Mass Index of Staff of Rivers State College of Health Science and Management Technology, Port Harcourt, Rivers State (IPS Journal of Public Health, 2024)
This study assessed the impacts of nutrition on blood pressure and body mass index of staff of Rivers State College of Health Science and Management Technology, Port Harcourt. Introduction: The nutritional status of an individual is said to be a measure of the condition of health of an individual as affected or determined by the intake of food and the utilization of nutrients. The nutritional status of an individual should be assessed at regular intervals in order to avert undesirable health problems and complications arising from malnutrition. Methodology:  The study adopted a descriptive survey research design and 100 respondents’ were randomly selected and administered with pretested and validated questionnaire. The blood pressure and anthropometric measurement were taken according to standard procedures. Result The result showed that 33.0% of the Respondents’ had normal BM1, 29.0% were overweight, while 38.0% were obese. The result further revealed that BMI increased with advance in age, as 18.0% and 38.0% of the Respondents’ aged 38- 60years had incidence of overweight and obesity respectively. Blood pressure values also showed a similar trend as Respondents’ aged 38 -60 years had 33.0% of Respondents’ have high blood pressure. Correlation coefficient between BMI and income showed a very high relationship (r= 0.9), which indicates that as income increased, BMI also increased. The relationship between income and blood pressure was poor (r = 0.2). However, exercise and blood pressure had a high correlation (r = 0.7). Similarly, alcohol consumption and blood pressure showed a good relationship (r = 0.6).These findings thus reflect the need for enlightenment of the masses on healthy lifestyles through healthy eating habits, regular exercise, and reduction in alcohol consumption in order to minimize the risk of high blood pressure. Conclusion: The study concluded that most of the people with high blood pressure are those with overweight and obesity; and high earning status and high consumption of alcohol could have serious consequences on health, as alcohol is a lifestyle factor related to high blood pressure.
Keywords: Body Mass Index; Blood Pressure; Nutritional status; BP; Anthropometric Measurements